Performance in major league baseball pitchers after surgical treatment of thoracic outlet syndrome - Gutman, M. J.; Gutman, B. S.; Joyce, C. D.; Kirsch, J. M.; Sherman, M. B.; Namdari, S. (The Physician and Sportsmedicine, 2022)
Introduction Thoracic outlet syndrome (TOS) can be a career-threatening injury for Major League Baseball (MLB) pitchers, often requiring surgical management. The purpose of this study is to determine the efficacy of surgical management for TOS as a function of return to play and quantitative pitching metrics.